Seasonal enrichment of heavy isotopes in meltwater runoff from Haig Glacier, Canadian Rocky Mountains - Penn, Kristina; Marshall, Shawn J.; Sinclair, Kate E. (Frontiers in Earth Science, 2023)
Glaciers provide an important source of freshwater, particularly during dry years and late in the summer, after most of the seasonal snow has melted. Glaciers are losing mass in most of the world’s mountain regions, which leads to uncertainties around the availability of freshwater to the downstream catchments. While contributions of glacial meltwater to rivers can be quantified through hydrograph separation methods, changes in the chemical characteristics of glacial meltwater may impact these calculations. We collected samples of supraglacial snow and ice and proglacial stream water over the course of a melt season at Haig Glacier in the Canadian Rocky Mountains and analyzed these samples for stable water isotopes (oxygen-18 and deuterium) and dissolved major ions to assess their seasonal variability. We identify isotopic enrichment in stable water isotopes on the surface of Haig Glacier as dry snow turns to wet snow and eventually in the bare ice that remains. This enrichment is reflected in isotopic ratios in the proglacial stream. Two possible explanations include: 1) isotopic enrichment through sublimation or liquid water evaporation on the glacier surface, 2) isotopic fractionation during diurnal freeze-thaw cycles, with the heavier isotopes preferentially refreezing. We evaluate each of these scenarios and conclude that evaporation effects are sufficient to explain the observed isotopic enrichment in the glacial runoff, although both processes may be acting simultaneously.